Elevated expression of IGFL1 indicates unfavorable prognosis in lung adenocarcinoma through promotion of cell proliferation and inhibition of apoptosis - Wang, Zhuo; Liang, Xiaoqin; Wang, Xiaojun; Yu, Qin (Polish Journal of Pathology, 2021)
Non-small cell lung cancer (NSCLC) is one of the principal causes of death worldwide. The disease is often diagnosed late, at the stage of metastasis, which leads to a poor prognosis. With currently available treatment, most patients experience relapse and drug resistance. This study aimed to determine the potential role of insulin growth factor-like family member 1 (IGFL1) in lung adenocarcinoma (LUAD). We analyzed the expression of IGFL1 using TIMER, UALCAN, and GEPIA. The association of IGFL1 expression with symptoms and overall survival (OS) in LUAD patients was evaluated using a tissue microarray (TMA). Moreover, A549 and H1299 cells with selective IGFL1 knockdown were used to observe their proliferation and apoptosis in vitro. From the TIMER, UALCAN and GEPIA databases, we found that IGFL1 was upregulated in LUAD (p < 0.001). The level of promoter methylation in IGFL1 was significantly downregulated in LUAD and patient groups with different gender. Similar results were obtained in UALCAN. The semi-quantitative analysis revealed that IGFL1 expression is correlated with TNM stage (p < 0.001) and tumor size (p < 0.001) in TMA. High levels of IGFL1 expression were associated with poor OS (p < 0.05). Functional tests in A549 and H1299 cells showed that knocking down the expression of IGFL1 inhibited proliferation and enhanced apoptosis. Our study revealed the potential utility of IGFL1 as a predictive biomarker, which may play a biological role by regulating the proliferation and apoptosis of tumor cells.